Cognitive disturbances at psychical disorders at patients with hypertensive encephalopathy: efficacy of treatment and rehabilitation measures - Дзюба, Олександр Миколайович; Толмачов, Олексій Анатолійович (ScienceRise: Medical Science, 2016)
Aim – to determine the clinical-psychopathological risk factors of the early development of psychical disorders in patients with hypertensive encephalopathy. Methods: informational-analytical, clinical-anamnestic, clinical-neurological, psycho-diagnostic, statistical. Results. It was established, that psychic disorders in persons with hypertensive encephalopathy can be corrected not only by medicamental means, directed on normalization of arterial pressure, but it is also possible to add the cognitive training of patients to the rehabilitation process that gives the significant medical-social effect. Conclusions: The solution of problem is in the plane of interdisciplinary studies that are concentrated on the neurological-psychological status of patients